Wastewater Channel And Escherichia Coli In Wells, Desa Durin Simbelang Kecamatan Pancur Batu - Seri Asnawati Munthe; Lia Rosa Veronika Sinaga; Jasmen Manurung (TOUR HEALTH JOURNAL, 2022)
Background :    Water  is  the  most  important  substance  in  life. About  three  quarters  of  our  body  consists  of  water  and  no person can  survive more than 4-5 days without drinking water. Water is used for cooking, washing, bathing, and cleaning waste. around  the  house.  Water  is  also  used  for  industrial  purposes, agriculture,  fire  fighting,  recreation,  transportation,  and  others. Water   can   spread   and   transmit   disease   to   humans.   These conditions   can   certainly   cause   disease   outbreaks.   can   be separated   from   human   life.   Clean   water   contaminated   with Escherichia coli bacteria is one of the causes of diarrheal disease. Purpose: The purpose   study   is   to   know   relationship   of wastewater  channel and  Escherichia  Coli  Levels  In  Wells,  Durin Simbelang Village, Pancur Batu District. Method: This  study  used  an  analytical  survey  method  with  a cross   sectional   design   using   simple   random   sampling.   The number of samples is 30 dug wells and statistical analysis using Chi square test. Results:  There  is  53.3%  of wastewater  channel with  high contamination  risk  and  56.7%  of  dug  wells  contaminated  with Escherichia  coli  bacteria.  From  the  statistical  results,  it  was found   that   there   was   a   relationship   between   sanitation   in wastewater channel(p value 0.269) with E.Coli content. Conslusion:  the  advice  given  by  the  researcher  is  that  if  it  is used  as  drinking  water,  it  should  be  boiled  until  it  boils,  giving disinfectant to dug wells to make it safer to use for hygiene and sanitation needs.